Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi Berbasis Web dengan Metode Simple Additive Weighting - Sholihat, Anisa; Gustian, Dudih (STIKOM Tunas Bangsa Pematangsiantar, 2022)
In educational institutions, in determining the order in which students who excel are generally selected only based on their final grades, the same is true in the Dwi Warna Vocational School. The ranking of students who excel at SMK Dwi Warna Sukabumi is only determined based on the value of the final report which ranks 1 to 5 only. In the process of selecting outstanding students there is an opportunity to make decisions that are not on target because the selection process for outstanding students is only based on one aspect of assessment, namely the value in the student's final report, meanwhile additional values such as attitude and achievement values that have been obtained are not from within. The school is not used as an assessment material and is also not used as a criterion in determining the order of students who excel. From this description, it is possible that the selected outstanding student does not meet the desired standard. Therefore, it takes a decision support system in the form of a website to make it easier and faster for the selection of outstanding students, with several methods that can be used and the Simple Addive Weighting (SAW) method by giving weighting to each of the criteria used. The system created is by using the PHP programming language. The system created is expected to be able to speed up the decision-making process in determining outstanding students